Knowledge Management and Intellectual Capital - A Theoretical Perspective of Human Resource Strategies and Practices - Budiarti, Isniar (European Journal of Economics and Business Studies, 2017)
Significant debates on the role of human resources have been shifted from organizational assets to initiator of innovation and competitive advantages. A current research has investigated suggestive roles of intellectual capital (IC) in strategic human resource management (SHRM) process and human research management (HRM) practices. Conversely, others have shown that the successful management of IC has related to implementation of knowledge management (KM). In turn, those perspectives suggest the implementation and usage of KM ensure the growth of IC, and the innovative IC may become an effective human resources strategies and practices to acquire innovation and competitive advantages. Through a comprehensive analysis of the latest journals on those concepts, this study argues that human resource strategies and practices involving KM and management of IC give potential oppurtunities to gain innovation and competitive advantages. Besides, this theoretical perspective suggests organizational culture and leadership style are interrelated to the process.
Keywords: intellectual capital, knowledge management, Human resource strategies, Human resource practices.